Antiviral activities of curcumin and 6‐gingerol against infection of four dengue virus serotypes in A549 human cell line in vitro - Jonathan Alvin Nugraha Halim; Stefanie Natalia Halim; Dionisius Denis; Sotianingsih Haryanto; Edi Dharmana; Rebriarina Hapsari; R. Tedjo Sasmono; Benediktus Yohan (Universitas Gadjah Mada, 2021)
Dengue virus (DENV) is the most geographically widespread arbovirus causing dengue disease epidemics in tropical and subtropical regions. Nature provides abundant plants as a source for lead molecules against various diseases including DENV infection. We investigated the antiviral effect of curcumin and 6‐gingerol, the major active constituent of turmeric (Curcuma longa Linn.) and ginger (Zingiber officinale Roscoe), respectively, against all four serotypes of DENV infecting human lung epithelial carcinoma (A549) cell line in vitro. Both compounds generated cell cytotoxicity to A549 cells at CC50 values of 108 µM for curcumin and 210 µM for 6‐gingerol. The compound curcumin showed antiviral properties as described by IC50 of 20.60, 13.95, 25.54, and 12.35 µM, while 6‐gingerol of 14.70, 14.17, 78.76, and 112.84 µM for DENV‐1, ‐2, ‐3, and ‐4, respectively. Different levels of antiviral properties were observed between DENV serotypes. Our findings suggest that the antiviral assay of compounds against DENV should be performed to all four serotypes and not limited to a particular serotype. In conclusion, curcumin and 6‐gingerol exhibit antiviral properties against DENV infection and could provide a new therapeutic approach for dengue disease treatment strategies.